2019
DOI: 10.1080/08870446.2019.1690146
|View full text |Cite
|
Sign up to set email alerts
|

How acceptable is a weight maintenance programme for healthy weight young women who are at increased risk of breast cancer?

Abstract: Objective: To determine if a weight gain prevention intervention is acceptable to young women with a normal Body Mass Index and a moderately increased or high risk of breast cancer. Design: Qualitative semi-structured interview study involving 14 women aged 26-35 years who were registered with a Family History Clinic in Manchester, UK, due to family history of breast cancer. Participants' views were analysed thematically. Results: Four themes were produced: 1) perceptions of a healthy lifestyle: women's percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Recruitment from within the MFT FHRPC: We have successfully recruited to health behavior research studies and PPI projects using postal invite letters to FHRPC participants with an uptake of between 9% and 23% (unpublished, in press, and [ 14 ]). Based on a 15% predicted uptake, 200 letters will be posted to recruit 30 women.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment from within the MFT FHRPC: We have successfully recruited to health behavior research studies and PPI projects using postal invite letters to FHRPC participants with an uptake of between 9% and 23% (unpublished, in press, and [ 14 ]). Based on a 15% predicted uptake, 200 letters will be posted to recruit 30 women.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous interview study reported that young women (aged 25-35 years) at increased risk of breast cancer are interested in joining a program to prevent weight gain and promote healthy behaviors which could be accessed remotely, potentially via an app [ 14 ]. This was in line with the views expressed by our public and patient involvement (PPI) group of women younger than 40 years at increased risk of breast cancer who had been a healthy weight at age 18 years but had since gained at least a stone in weight (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, women who previously received 10-year breast cancer estimates were more likely to report changes to diet, alcohol consumption and physical activity if they self-reported being high risk [ 35 ]. Offering specific interventions such as programmes focused on weight loss or weight gain prevention appear to be beneficial for women at higher risk of breast cancer [ 36 39 ]. The findings in the present study suggest it may also be feasible to prevent weight gain in women at lower risk of breast cancer given they reported the desire to maintain this level of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other studies have been implemented to evaluate the possibility to change lifestyle habits in high-risk young women [ 26 , 27 ]. Among them the LivingWell study demonstrated that a lifestyle program for people with a FH of BC cancer is feasible and the results suggest favorable outcomes in terms of PA increase and reduction in dietary fat [ 26 ].…”
Section: Discussionmentioning
confidence: 99%